Effect of Added Mass Location on Manual Wheelchair Propulsion Forces - Alcoléa, Vitor [UNESP]; Medola, Fausto Orsi [UNESP]; da Silva Bertolaccini, Guilherme [UNESP]; Sandnes, Frode Eika (Springer Nature, 2020)
This study investigated the influence of mass distribution on the handrim forces during manual propulsion in four different mobility tasks: Straightforward motion at self-selected speed; straightforward sprint; zero radius turn; and circular trajectory. A foldable-frame wheelchair was instrumented with a SmartWheel system placed on the right side. Three different positions of an additional mass of 7.8 kg were investigated: In the center of the rear wheels’ axle; on the spokes of each of the two rear wheels; under the footrest. When mass is added in a centered position, there is little effect on the level of forces required to propel the chair, while when the additional mass is positioned distant to the wheelchair center, namely rear wheels’ spokes and feet support, the effect on propulsion forces is increased. Optimizing wheelchair mobility efficiency requires an understanding on the effects of changes in equipment configuration on propulsion kinetics.
Keywords: Mass distribution; Mobility; Propulsion kinetics; Wheelchair configuration; Wheelchairs